KAJIAN PERSEPSI PEMILIK USAHA KECIL DAN MENENGAH (UKM) TERHADAP LAPORAN KEUANGAN - R. Adisetiawan (Universitas Batanghari Jambi, 2013)
The information is useful data obtained so it can be relied upon to take the right decision. The information has potential value because of information contributes directly in determining the alternative actions that berbabagai can be used as consideration in the planning, control and decision making. Financial accounting information related to accounting data for financial transactions from one organizational unit that engaged in business, good business services, trade, business and industrial enterprises. The financial information in the form of financial statements and provide benefits very much needed by the management company in formulating decisions in solving all the problems faced by the company. Because of the company's financial statements can be obtained information about the performance of the company's cash flow, and other information relating to the financial statements.In this research use analyses conducted include (1) a person, that includes about the existence or whereabouts of a person who has expertise or special knowledge about accounting, (2) units, that is one part or a collection of some of the people in the company and is responsible for part of it, in this case more research focused on the existence of the company's accounting unit, (3) process, which can be said to be an activity that includes record-keeping, categorization, compaction, reporting, and financial data penganalisisan a oragnisasi or a company (Jusuf, 1992: 4), (4) training or coaching is among the efforts made by the company in order to enhance the knowledge and capabilities, especially in the accounting field skills and knowledge, in this case how far implementation, (5) technology, which is one of the components or equipment in the company's business activities are assessed can provide many benefits and advantages for its usersand can assist the user in creating and presenting financial statements.Key words: Financial accounting information